2013
DOI: 10.5194/tc-7-349-2013
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends in Laptev Sea ice outflow between 1992–2011

Abstract: Abstract. Variability and trends in seasonal and interannual ice area export out of the Laptev Sea between 1992 and 2011 are investigated using satellite-based sea ice drift and concentration data. We found an average total winter (October to May) ice area transport across the northern and eastern Laptev Sea boundaries (NB and EB) of 3.48 × 10 5 km 2 . The average transport across the NB (2.87 × 10 5 km 2 ) is thereby higher than across the EB (0.61 × 10 5 km 2 ), with a less pronounced seasonal cycle. The tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 52 publications
2
54
0
Order By: Relevance
“…This is in accordance with a general trend of accelerating early ice retreat in the Laptev Sea, probably because of thinner sea ice (Krumpen et al, 2013). Based on our observations, on average, the open water season starts on 20 July.…”
Section: Changes In Environmental Parameterssupporting
confidence: 72%
“…This is in accordance with a general trend of accelerating early ice retreat in the Laptev Sea, probably because of thinner sea ice (Krumpen et al, 2013). Based on our observations, on average, the open water season starts on 20 July.…”
Section: Changes In Environmental Parameterssupporting
confidence: 72%
“…Hence, positive trends in both POLA and IP not only fit well to the previously estimated positive trend in IP from Iwamoto et al (2014) but also to the positive trend of 0.85 × 10 5 km 2 per decade in the Laptev Sea ice area flux . Other linkages and dependencies with the Arctic sea-ice extent in September (annual minimum), the timing of the freeze onset and further connections to large-scale atmospheric circulation patterns are very likely and have been proposed by various previous studies (e.g., Alexandrov et al, 2000;Deser et al, 2000;Rigor et al, 2002;Willmes et al, 2011;Krumpen et al, 2013). In particular, a significant lengthening of the melt season in recent years, and hence a later freezeup in autumn, already seems to imprint on the derived POLA (i.e., thin-ice area) and IP estimates in the early winter period (Markus et al, 2009;Parkinson, 2014;Stroeve et al, 2014).…”
Section: Regional Focus -Laptev Seamentioning
confidence: 99%
“…In some cases, the shape of these areas resembles an arch-type pattern of an ice bridge mechanism, a feature that commonly appears in the Nares Strait between Ellesmere Island and Greenland, for example (Williams et al, 2007). Krumpen et al (2013) discovered that most of the ice being incorporated in the Transpolar Drift originates from the western and central part of the Laptev Sea. Furthermore, it is indicated that the contribution from polynyas, while being generally small, is limited to events in the proximity of the Laptev Sea boundaries.…”
Section: Regional Focus -Laptev Seamentioning
confidence: 99%
See 1 more Smart Citation
“…The Laptev Sea (Siberia) is a very shallow shelf sea with water depths between 15 and 200 m and comprises an area of about 500 × 10 3 km 2 (Timokhov, 1994;Krumpen et al, 2013). It is one of the most significant regions where a considerable amount of the total Arctic sea ice is produced (Aagard et al, 1981;Dmitrenko et al, 2009;Dethleff et al, 1998;Willmes et al, 2011a;Tamura and Ohshima, 2011;Iwamoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%